PROXIMATE, TANNIN, AND AMYLOSE IN SIX SORGHUM VARIETIES ACROSS TWO PLANTING SEASONS - Arif Muazam; Kristamtini Kristamtini; Setyorini Widyayanti; Yudhistira Nugraha; Rina Sri Kasiamdari; Budi Setiadi Daryono (SEAMEO BIOTROP, 2025)
ARTICLE HIGLIGHTS- Sorghum nutrition varies across varieties and growing seasons- Dry season increases starch and amylose content in some varieties- Rainy season enhances protein levels in sorghum grains- Genotype-environment interaction affects sorghum nutritional quality- Sorghum adaptation supports food diversification and climate resilienceABSTRACTSorghum (Sorghum bicolor (L.) Moench) is a potential staple food in Indonesia, offering an alternative to rice and corn due to its adaptability to marginal lands and drought tolerance. However, research on the impact of environmental factors, particularly different growing seasons, to the nutritional composition of sorghum varieties are still lacking. This study aimed to analyze the proximate contents of tannin and amylose in six sorghum varieties cultivated in two different planting seasons (wet and dry seasons). A Completely Randomized Design with three replications was applied in this experiment. The tested varieties included three newly developed superior varieties (Bioguma, Samurai, and Kawali) and three local varieties (Black Bonteb, Red Glutinous Sorghum, and KD4). The results showed that proximate composition varied across varieties and seasons. Starch content was generally higher in the dry season, with the highest observed in Kawali (64.16%) and Bioguma (63.11%), while the lowest was in Black Wareng (11.99%). Similarly, protein content peaked in Black Wareng (7.68%) and Red Glutinous Sorghum (7.37%), but was the lowest in Samurai (4.48%). Tannin levels also fluctuated by season, where Bioguma, KD4, and Kawali exhibited higher tannin content in the dry season, whereas Samurai, Red Glutinous Sorghum, and Black Bonteb had lower tannin levels. Notably, amylose content was significantly higher in Red Glutinous Sorghum (4.72%) and Black Bonteb (4.62%) across both seasons, contributing to their fluffier texture when cooked. These findings highlight the influence of environmental conditions on sorghum nutritional quality, reinforcing its potential for food diversification, including processed sorghum flour as a substitute for wheat flour.